The effectiveness of medical device logistics management at Puskesmas X in supporting healthcare service optimization - Rizky, Ayu; Mayarestya, Nita Putriasti; Hastuti, Lidia; Arfan, Iskandar; Marlenywati, Marlenywati (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2024)
Background: Optimal healthcare services at community health centers require effective logistic management to ensure adequate availability of medical devices. At Puskesmas X, there are several issues related to the availability and management of medical devices that affect the quality of healthcare services. This study aims to analyze the logistic management of medical devices at Puskesmas X as a basis for planning a logistic management improvement program. Method: This research uses a descriptive method with a qualitative approach. Data were collected through in-depth interviews with community health center staff and direct observation at the research site. Data analysis was conducted using thematic analysis. Results: The results show that the logistic management of medical devices at Puskesmas X is not yet optimal. There are deficiencies in planning, procurement, and storage of medical devices, as well as frequent delays in reporting. The main factors influencing this are the frequent turnover of goods treasurers and the lack of training for logistics staff. Conclusion: Improvements in the logistic management of medical devices at Puskesmas X are needed through enhancements in planning, procurement, and storage systems, as well as training for logistics staff to ensure adequate availability of medical devices and improved quality of healthcare services.